Comparison of Iris Fixated and Scleral Fixated intra Ocular Lens for Correction of Aphakia in Traumatic Cataract with no Proper Capsular Support - Shirzadi, Keyvan; Tabatabaei, Seyed Ali; Tabatabaei, Seyed Mehdi; Soleimani, Mohammad (Journal of Ophthalmic and Optometric Sciences, 2019)
Purpose: To compare visual outcomes and complications of iris fixated and scleral fixated intra ocular lens (IOL) implantation in patients suffering from traumatic cataract with no proper capsular support. Patients and Methods: This prospective interventional study was performed in Farabi Eye Hospital, Tehran, Iran, between May 2015 and May 2016. Twenty five patients with traumatic cataract and no proper capsular support for IOL implantation in the bag or sulcus were included and randomly underwent either iris fixated or sulcus fixated IOL implantation. Follow up visits were performed one day, one week, four weeks, three months and six months after surgery. In each visit visual acuity, intra ocular pressure, placement of IOL and anterior chamber reaction were studied. Results: Thirteen eyes of 13 patients underwent iris fixation and 12 eyes of 12 patients underwent scleral fixation of IOL. The average patient age at presentation was 29.12 ± 16.32. In the follow up visit one week after IOL fixation three patients in each group had significant anterior chamber inflammation. There was no statistically significant difference between the two groups regarding the number of patients with elevated IOP (P = 0.96), dislocated IOL (P = 0.480) and complications such as wound dehiscence and iridocorneal adhesion. Also no statistically significant difference regarding the mean BCVA three months after surgery was observed (P = 0.55). Conclusion: We did not observe any significant difference in outcome of iris and scleral fixation of IOL in traumatic eye injuries with no effective capsular support.